Teacher Training in Chile: a critical perspective as regards the historical dilemma of educational changes (Praxis Educativa, 2015)
This paper discusses pre-service teacher training in Chile from a critical perspective related to the historical transformation in which it takes place. This analysis was based on an institutional framework which allowed it to expand in a steady and consistent way. The consolidation scene of this process was altered by the emergence of the military government, which introduced a new structure supported by an economic model that led to an exacerbated enrollment expansion and brought about deregulation and low quality. This situation, despite the efforts of recent governments, has not been reversed yet.
Keywords: pre-service teacher training; history; quality; coverage; challenges